Radionuclide contamination in soil and radiological hazard assessment from industrial areas: a systematic review - Abd Bahar, Supiah; Mohamad Fandi, Noor Fatihah (IIUM Press, 2024)
Background: The production of radionuclides as industrial by-products such as radium (226Ra), thorium (232Th), potassium(40K), and uranium (238U) might contaminate the soil and harm the health of nearby populations for long-term. Due to the limited evidence of the associated relation and lack of public awareness of the potential risk, people tend to ignore this concerning issue. Therefore, this study aims to review the activity concentrations of the aforementioned radionuclides in the soil's nearest industrial vicinity and to assess their radiological hazard presented in the existing literature. Method: This systematic review was conducted using Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA 2009) on online databases such as PubMed, SpringerLink, Scopus, and ProQuest. The following criteria were included: full-text English journal, studies from 2014 onwards with search keywords of “radionuclide exposure” AND “radiological hazard” OR “health effect”. Results: A total of 1025 articles were screened and only 7 full-text articles were evaluated. Based on the review, the types of industries that produce 226Ra, 232Th, 40K, and 238U were petrochemical, chemical, rare-earth element (REE), and gold mining industries. The findings showed the elevated 226Ra activity, nearly three times the global average of 35 Bq/kg, was found at petrochemical sites in Rayong, Thailand. The 232Th and 40K activity levels at Nigeria mining sites were higher than the global average. All studied areas exceeded world average for 238U. The highest absorbed dose (D) values were observed in artisanal mining, Anka, Nigeria (127.00 nGy/h) and in petrochemical sites in Rayong, Thailand (84.98 nGy/h), both exceeding the limit of 60 nGy/h. The annual outdoor effective dose (AED) from similar industrial areas was 2.2 and 1.4 times higher than the global average of 0.07 mSv/y. The highest gamma index (Iγr) value was at 2.08, recorded in Anka artisanal mining area, exceeding the safe limit of 1. Meanwhile, all values for excess lifetime cancer risk (ELCR) were below a safe limit of 1.16 × 10⁻³. Conclusion: In conclusion, radiological risks at Anka artisanal mining sites and Rayong petrochemical sites, exceeded UNSCEAR limits, but cancer risks were minimal, suggesting a need for further research including in groundwater samples and clinical studies.